Implementasi Sistem Pendukung Pengambilan Keputusan pada Pembelian Bahan Olahan Karet dari Pemasok - Luthvina, Ridha; Hadiguna, Rika Ampuh; Jonrinaldi, Jonrinaldi (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
The need for high-quality crumb rubber in West Sumatra tends to increase. However, the amount and quality of rubber from suppliers belong to weak caused by the bad monitoring systems, the supply cannot be met properly, and there is a lot of shrinkage in rubbers purchased by the company. Therefore this research was carried by implementing the Decision Support System (DSS) which was expected to help facilitate supplier data searches and evaluate the supplier's performance. The first stage in this research was designing DSS included the use of Unified Modeling Language (UML) diagram and database design. Next, built an applicable software using Personal Home Page (PHP), My Structured Query Language (MySQL), and Apache. An advantage of DSS designed was to accommodate differences and changes in rubber supplier assessment criteria according to the consideration of each crumb rubber industry in West Sumatra. There were 3 of 11 main crumb rubber criteria assessed. The results of these 3 criteria were obtained highest weight, namely Dryness (0.18), cleanliness (0.15), and consistency of quality (0.10). While the previous performance obtained the lowest weight (0.05). This meant that the criteria of dryness, cleanliness, and consistency of quality, will be the main considerations for companies in ranking and evaluating suppliers who work with companies.